Composite material and preparation method thereof, photoelectric device and display device

Through the use of the composite gradient of the price band in the OLEDS optoelectronic component, the problem of poor thermal stability of organic empty acupoint transmission materials is solved, and more efficient cavity injection and transmission are realized, and the performance and life of the optoelectric components are improved.

CN119384204APending Publication Date: 2025-01-28GUANGDONG JUHUA RES INST OF ADVANCED DISPLAY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310935551.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The organic hole transport materials used in existing optoelectronic devices such as OLEDs affect the application of materials and the performance and life of optoelectronic devices due to poor thermal stability.

Method used

Provide a composite material, including P -type metal oxides and first metal oxides. Promote the effective injection and transmission of acupuncture.

Benefits of technology

This composite material has good cave transmission performance and stability, which can improve the acupoint injection efficiency and photoelectric conversion efficiency of photoelectric components, and extend the life of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384204A_ABST
    Figure CN119384204A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material, a preparation method, a photoelectric device and a display device. The composite material comprises the p-type metal oxide and the first metal oxide, and the valence band energy level of the first metal oxide is lower than that of the p-type metal oxide, so that an energy level gradient is formed in the composite material, the hole injection barrier can be reduced, effective injection of holes can be promoted, and the hole transmission efficiency can be improved; good hole transport performance is realized. The composite material is an all-inorganic material, is less affected by water, oxygen and the like, and has better stability compared with an organic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display technology, and in particular to a composite material and a preparation method thereof, an optoelectronic device and a display apparatus. Background Art

[0002] At present, organic hole transport materials are usually used as materials for the hole functional layer in optoelectronic devices such as OLEDs, mainly because organic hole transport materials have good hole mobility and good processability. However, organic hole transport materials are easily destroyed by heat due to their organic structure, that is, they have poor thermal stability, which affects the application of organic hole transport materials and the performance and life of optoelectronic devices containing organic hole transport materials.

[0003] Therefore, it is very important to provide a hole transport material that has both good hole transport performance and good stability. Summary of the invention

[0004] In view of this, the present application provides a composite material and a preparation method, an optoelectronic device and a display device, aiming to provide a composite material that has good hole transport performance and good stability.

[0005] The embodiments of the present application are implemented as follows: In a first aspect, a composite material is provided, comprising a p-type metal oxide and a first metal oxide, wherein a valence band energy level of the first metal oxide is lower than a valence band energy level of the p-type metal oxide.

[0006] In a second aspect, an embodiment of the present application also provides a method for preparing a composite material, comprising: providing a first mixture, the first mixture comprising a p-type metal oxide and a first solvent, the first solvent comprising a hole sacrificial agent; after subjecting the first mixture to a first light treatment, adding an organic first metal salt to the first mixture, and continuing the second light treatment to obtain a composite material; wherein the valence band energy level of the first metal oxide corresponding to the organic first metal salt is lower than the valence band energy level of the p-type metal oxide.

[0007] In a third aspect, an embodiment of the present application further provides a photoelectric device, comprising: a hole functional layer, wherein the material of the hole functional layer comprises the composite material as described above, or comprises a composite material obtained by the preparation method of the composite material as described above.

[0008] In a fourth aspect, an embodiment of the present application further provides a display device, comprising the light-emitting device as described above.

[0009] The composite material of the present application includes a p-type metal oxide and a first metal oxide, wherein the valence band energy level of the first metal oxide is lower than the valence band energy level of the p-type metal oxide, and an energy level gradient is formed in the composite material, which can reduce the hole injection barrier, promote the effective injection of holes, improve the hole transport efficiency, and have good hole transport performance. Moreover, the composite material is a fully inorganic material, which is less affected by water, oxygen, etc., and has better stability than organic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0011] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a composite material provided in the present application;

[0012] Figure 2 A structural schematic diagram of an embodiment of a light emitting device is provided for the present application.

[0013] Figure 3 A schematic diagram of a process of an embodiment of a method for preparing a light-emitting device provided in the present application;

[0014] Figure 4 A schematic diagram of another embodiment of a method for preparing a light-emitting device provided in the present application;

[0015] Figure 5 and Figure 6 AFM images of the hole functional layer in device comparative example 1 and device embodiment 2 respectively;

[0016] Figure 7 EQE-J curves of device embodiments 1-5 and comparative examples 1-2;

[0017] Figure 8 EQE-J curves of device example 6 and comparative examples 1 and 3;

[0018] Fig. 9 EQE-J curves of device embodiments 7-8 and comparative examples 1 and 4;

[0019] Fig.10 EQE-J curves of device examples 9-10 and comparative examples 1 and 5;

[0020] Fig.11 JV curves of single hole devices of device embodiments 1-10;

[0021] Fig.12 JV curves of single hole devices of device embodiment 6 and comparative examples 1-5;

[0022] Fig.13 The voltage-time curves of the single hole devices of device examples 1-5 and comparative examples 1-2;

[0023] Fig.14 The voltage-time curves of the single hole devices of device example 6 and comparative examples 1 and 3;

[0024] Fig.15 The voltage-time curves of the single hole devices of device examples 7-8 and comparative examples 1 and 4;

[0025] Fig.16 The voltage-time curves of the single hole devices of device examples 9-10 and comparative examples 1 and 5;

[0026] Figure 17-21 These are the valence band position diagrams of copper oxide, molybdenum oxide, manganese oxide, chromium oxide, and cobalt oxide respectively.

[0027] Reference numerals: light emitting device 100 ; first electrode 10 ; second electrode 20 ; light emitting layer 30 ; hole functional layer 40 ; electron functional layer 50 , electron injection layer 51 , electron transport layer 52 . DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise specified, the directional words such as "upper" and "lower" used are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the stated range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited numeral (fractional or integral) within the stated range.

[0029] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0030] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0031] In the present application, "ring atoms" means the number of atoms of the ring atoms constituting the ring itself in a structural compound (e.g., a monocyclic compound, a condensed ring compound, a cross-linked compound, a carbocyclic compound, a heterocyclic compound) formed by atoms bonding to form a ring, i.e., the number of atoms forming the ring. When the ring is substituted by a substituent, the atoms contained in the substituent are not included in the ring atoms. The same is true for the "ring atoms" described below, unless otherwise specified. For example, the number of ring atoms of a benzene ring is 6, the number of ring atoms of a naphthalene ring is 10, and the number of ring atoms of a thienyl group is 5.

[0032] In the present application, "aryl or aromatic group" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing a hydrogen atom, which can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic rings, at least one is an aromatic ring system. For example, "aryl having 5-30 ring atoms" refers to an aromatic group containing 6 to 30 ring atoms, and the aromatic group can be optionally further substituted. Preferably, substituted or unsubstituted aromatic groups having 6 to 24 ring atoms are used, more preferably substituted or unsubstituted aromatic groups having 6 to 18 ring atoms are used, and particularly preferably substituted or unsubstituted aromatic groups having 6 to 14 ring atoms are used, and the aromatic group can be optionally further substituted; suitable examples include, but are not limited to, phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, phenanthrenyl, fluoranthenyl, triphenylene, pyrenyl, perylene, naphthyl, fluorenyl, dinaphthylenyl, acenaphthene and derivatives thereof. It is understandable that multiple aromatic groups may also be interrupted by short non-aromatic units (e.g. <10% non-H atoms, such as C, N or O atoms), specifically acenaphthene, fluorene, or 9,9-diarylfluorene, triarylamine, diaryl ether systems should also be included in the definition of aromatic groups.

[0033] In the present application, "heteroaryl or heteroaromatic group" means that at least one carbon atom is replaced by a non-carbon atom on the basis of an aromatic group, and the non-carbon atom can be an N atom, an O atom, an S atom, an Si atom, a P atom, etc. For example, "heteroaryl having 5-30 ring atoms" means a heteroaryl having 5 to 30 ring atoms, preferably a substituted or unsubstituted heteroaryl having 5 to 24 ring atoms, more preferably a substituted or unsubstituted heteroaryl having 5 to 18 ring atoms, and particularly preferably a substituted or unsubstituted heteroaryl having 5 to 14 ring atoms, and the heteroaryl is optionally further substituted; suitable examples include, but are not limited to: thienyl, furanyl, pyrrolyl, oxadiazolyl, triazolyl, imidazolyl, pyridyl, bipyridyl, pyrimidyl, triazinyl, Acridinyl, pyridazinyl, pyrazinyl, quinolyl, isoquinolyl, quinazolinyl, quinoxalinyl, phthalazinyl, pyridopyrimidinyl, pyridopyrazinyl, benzothienyl, benzofuranyl, indolyl, pyrroloimidazolyl, pyrrolopyrrolyl, thienopyrrolyl, thienothiphenyl, furopyrrolyl, furofuranyl, thienofuranyl, benzisoxazolyl, benzisothiazolyl, benzimidazolyl, o-naphthyl, phenanthridinyl, primary pyridyl, quinazolinone, dibenzothienyl, dibenzofuranyl, carbazolyl and derivatives thereof.

[0034] The present application provides a composite material, including a p-type metal oxide and a first metal oxide, wherein the valence band energy level of the first metal oxide is lower than the valence band energy level of the p-type metal oxide. In this embodiment, the p-type metal oxide belongs to a p-type semiconductor material, and the p-type semiconductor material is a semiconductor material that is mainly hole-conducting. That is, there are two types of carriers in the p-type metal oxide, namely, holes in the valence band and electrons in the conduction band, but holes are mainly conductive.

[0035] In this embodiment, the composite material has good hole transport performance and can be used as a material for a hole functional layer. The valence band energy level of the first metal oxide is lower than the valence band energy level of the p-type metal oxide, so an energy level gradient is formed in the composite material, which can reduce the hole injection barrier, promote the effective injection of holes, and improve the hole transport efficiency. Moreover, the composite material is a fully inorganic material, which is less affected by water, oxygen, etc., and has better stability than organic materials. Furthermore, when the composite material is used as a hole functional layer in a light-emitting device, it can enhance the built-in electric field, promote the interface charge extraction between the hole functional layer and the adjacent film layer, and then reduce the non-radiative recombination of carriers, thereby improving the photoelectric conversion efficiency of the light-emitting device and improving the luminous efficiency of the light-emitting device.

[0036] In a specific embodiment, the valence band energy level of the first metal oxide is at least 0.1 eV lower than the valence band energy level of the p-type metal oxide, for example, the valence band energy level of the first metal oxide is 0.14 eV, 0.31 eV, or 0.34 eV lower than the valence band energy level of the p-type metal oxide. In one embodiment, the valence band energy level of the p-type metal oxide is between -4.7 and -5.2 eV, specifically -4.7 to -4.86 eV, -4.86 to -5.00 eV, -5.00 to -5.17 eV, -5.17 to -5.20 eV, etc. The p-type metal oxide with the valence band energy level in the range can facilitate the injection and transport of holes. Specifically, the p-type metal oxide may include one or more of CuO, MnO, In2O3, CoO, CrO3, etc.

[0037] In a specific embodiment, the p-type metal oxide is selected from CuO. In one embodiment, the average particle size of the p-type metal oxide is 3 to 10 nm, specifically 3 to 8 nm, 4 to 8 nm, 4 to 6 nm, 5 to 6 nm, etc. In one embodiment, the valence band energy level of the first metal oxide can be -4.90 to -5.20 eV, specifically -4.90 to -4.99 eV, -4.99 to -5.00 eV, -5.00 to -5.17 eV, -5.17 to -5.20 eV, etc. Further, the first metal oxide can include one or more of cobalt oxide, molybdenum oxide, chromium oxide, and manganese oxide.

[0038] In one embodiment, the first metal oxide is loaded on the surface of the p-type metal oxide, that is, the first metal oxide is loaded on the p-type metal oxide and connected to the p-type metal oxide. Specifically, the first metal oxide is loaded and connected to the p-type metal oxide in the form of particles, wherein the average particle size of the first metal oxide can be 2 to 5 nm, specifically 2 to 3 nm, 3 to 4 nm, 4 to 5 nm, etc.

[0039] In one embodiment, the first metal oxide is connected to the p-type metal oxide. Specifically, the first metal oxide is connected to the p-type metal oxide through the surface defects of the p-type metal oxide. For example, the first metal ions in the first metal oxide can occupy the metal vacancies and other related defect positions of the p-type metal oxide, thereby forming a bond connection. In addition, the valence band and conduction band of the p-type metal oxide are respectively composed of the O-2p electronic state and the ns electronic state of the metal. After light excitation, the electrons and holes of the p-type metal oxide are respectively gathered near the O-2p orbital and the ns orbital of the metal, so the metal ions in the first metal oxide are more likely to gather near the O-2p orbital to form a bond to form the first metal oxide.

[0040] In one embodiment, a negatively charged organic group is connected to the surface of the first metal oxide and / or the p-type metal oxide, and the organic group has the following structure:

[0041]

[0042] Wherein, each occurrence of R1, R2, R3, and R4 is independently selected from one or more of H, D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl; wherein X is halogen, selected from one or more of F, Cl, Br, and I.

[0043] It can be understood that the number of carbon atoms in the C1-C30 alkyl, the aryl having 5-30 ring atoms, and the alkyl, aryl or heteroaryl in the heteroaryl having 5-30 ring atoms can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30.

[0044] It can be understood that the aromatic group having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl specifically means that the H on the aromatic group having 5-30 ring atoms can be replaced by one or more of hydroxyl, -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.

[0045] Further, in one embodiment, each occurrence of R1, R2, R3, and R4 is independently selected from -NH2, C1-C10 alkyl, C1-C10 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and aryl having 5-24 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl. In a specific embodiment, each occurrence of R1, R2, R3, and R4 is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, phenyl, naphthyl, biphenyl, pyridyl, benzopyridyl, pyrimidyl, benzopyrimidyl, amino, and one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, phenyl, naphthyl, biphenyl, pyridyl, and pyrimidyl substituted with at least one of -OH, -X, methyl, ethyl, n-propyl, isopropyl, and n-butyl; X is halogen selected from one or more of F, Cl, Br, and I.

[0046] In one embodiment, R1 is selected from one or more of -NH2, -CH3, -CH2CH3, -CH2F, -CHF2, -CF3, phenyl, naphthyl, biphenyl, and tolyl; in one embodiment, R2, R3, and R4 are independently selected from one or more of -CH3, -CH2CH3, -CH2F, -CHF2, -CF3, phenyl, naphthyl, biphenyl, and tolyl.

[0047] In one embodiment, each occurrence of R1, R2, R3, and R4 is independently selected from the following groups:

[0048]

[0049] In the present application, "*" indicates a connection site or a fusion site. When the connection site is not specified in the group, it means that an optional connection site in the group is used as the connection site. When the fusion site is not specified in the group, it means that an optional fusion site in the group is used as the fusion site.

[0050] Furthermore, the organic group may include one or more of the following structural formulas:

[0051]

[0052] In this embodiment, the organic group is coordinated and connected to the surface of the first metal oxide and / or the p-type metal oxide, which can, on the one hand, increase the carrier density and promote the injection of holes; on the other hand, the organic group is coordinated and connected to the surface of the first metal oxide and / or the p-type metal oxide, and can combine with a large number of oxygen defects on the surface of the first metal oxide and / or the p-type metal oxide, thereby reducing the surface defects of the first metal oxide and / or the p-type metal oxide and improving the dispersibility and film-forming properties of the composite material.

[0053] In one embodiment, the mass ratio of the first metal oxide to the p-type metal oxide is 1-2:5 (i.e., 20%-40%), and can be specifically 20-35%, 25-35%, 25-30%, 20-23%, 35-40%, etc. The mass ratio of the first metal oxide to the p-type metal oxide can improve the hole injection performance of the composite material.

[0054] The present application also provides a method for preparing a composite material, see Figure 1 , Figure 1 This is a flow chart of an embodiment of a method for preparing a composite material provided by the present application, which specifically includes the following steps:

[0055] Step S11: providing a first mixture, wherein the first mixture includes a p-type metal oxide and a first solvent;

[0056] Step S12: After the first mixture is subjected to the first light treatment, an organic first metal salt is added to the first mixture, and the second light treatment is continued to obtain a composite material; wherein the valence band energy level of the first metal oxide corresponding to the organic first metal salt is lower than the valence band energy level of the p-type metal oxide.

[0057] In this embodiment, the first mixture is subjected to a first light irradiation treatment, and the p-type metal oxide can excite electrons (e - ), the electrons can react with the oxygen and water in the first mixture system to generate hydroxide, and after the organic first metal salt is added to the system, the first metal cation in the organic first metal salt can react with the hydroxide to generate the first metal oxide, and the second light treatment is continued, which can continuously promote the generation of electrons and improve the efficiency of the photocatalytic reaction. The method of this embodiment can generate the first metal oxide in situ. Among them, the reaction mechanism can be referred to as follows:

[0058]

[0059] Wherein, the first metal cation (M n+ ) can be a cobalt ion (Co 2+ ), molybdenum ion (Mo 3+ 、Mo 4+ Or Mo 6+ ), manganese ion (Mn 2+ The corresponding first metal oxide may be one or more of cobalt oxide, molybdenum oxide, and manganese oxide.

[0060] When the composite material is used as the material of the hole functional layer, the first metal oxide, the p-type metal oxide and the anode form an energy level gradient with gradually increasing valence band energy levels, which is beneficial to reducing the hole injection barrier and improving the hole injection and transport performance.

[0061] Furthermore, through the photocatalysis of the p-type metal oxide, the first metal cation in the organic first metal salt is prompted to generate the first metal oxide in situ, and the organic anion in the organic first metal salt can be connected to the surface of the p-type metal oxide, and can also be connected to the surface of the first metal oxide generated in situ, thereby reducing the defects of the first metal oxide and the p-type metal oxide, improving the hole injection and transport performance of the composite material, and effectively avoiding the regrowth and agglomeration of the nanoparticles of the first metal oxide and the p-type metal oxide, thereby improving the uniformity and film-forming performance of the particles in the composite material.

[0062] In addition, during the light treatment process, the holes (h+) generated by photocatalysis can effectively fill the defects on the surface of the p-type metal oxide (such as oxygen vacancies, etc.), play a role in passivating the p-type metal oxide, and can effectively avoid the regrowth of nanoparticles of the p-type metal oxide, improve the uniformity of the particles in the composite material, reduce agglomeration, and thus improve the film-forming property of the composite material.

[0063] In the step S11: the first metal oxide and the p-type metal oxide can refer to the related description of the composite material mentioned above, which will not be repeated here.

[0064] In one embodiment, the concentration of the p-type metal oxide in the first mixture is 40-80 mg / mL, specifically 40-70 mg / mL, 50-70 mg / mL, 50-60 mg / mL, 40-50 mg / mL, 70-80 mg / mL, etc. The first solvent includes one or more of an alcohol solvent with 1-8 carbon atoms, an ether solvent with 1-8 carbon atoms, tetrahydrofuran, acetone, chlorobenzene, toluene, etc. Specifically, the alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, n-butanol, n-octanol, glycerol, etc. The ether solvent includes one or more of methyl ether, ethyl ether, etc. In one embodiment, the first mixture also includes a hole sacrificial agent, which can consume the holes generated by photocatalysis, thereby providing more electrons to generate hydroxide. Further, the hole sacrificial agent can include one or more of acetonitrile, triethylamine, triethanolamine, sodium sulfite, methanol, ethanol, etc.

[0065] In one embodiment, the mass ratio of the hole sacrificial agent to the p-type metal oxide may be (0.5-1.5):5, specifically (0.5-1.3):5, (0.8-1.3):5, (0.8-1.0):5, (0.5-0.8):5, (1.3-1.5):5, etc. The mass ratio can provide an excess of the hole sacrificial agent to consume the holes generated in the photocatalytic reaction, and also avoid the waste of the hole sacrificial agent.

[0066] It can be understood that when the first solvent included in the first mixture includes solvent types listed in the hole sacrificial agent such as methanol and ethanol, the first solvent can have the function of a hole sacrificial agent and can consume holes, and at this time, there is no need to add the hole sacrificial agent additionally.

[0067] In one embodiment, before providing the first mixture, the method further includes: preparing a p-type metal oxide, specifically including the following steps: step S111: dissolving a p-type metal salt in a fourth solvent to obtain a p-type metal salt precursor solution; and dispersing a base in a fifth solvent to obtain an alkaline solution; step S112: adding the alkaline solution to the p-type metal salt precursor solution and stirring to obtain a p-type metal oxide.

[0068] In the step S111: the p-type metal salt is set accordingly according to the specific type of the p-type metal oxide. In a specific embodiment, the p-type metal oxide is copper oxide, and the p-type metal salt is a copper salt. Specifically, the copper salt can be selected from one or more of copper sulfate, copper chloride, copper bromide, copper oxalate, copper nitrate, anhydrous copper acetate, etc. In one embodiment, the concentration of the p-type metal salt in the p-type metal salt precursor solution can be 0.5M~2M, specifically 0.5M~1M, 1M~1.5M, 1.5M~2M, etc. In one embodiment, the fourth solvent can include one or more of methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, and glycerol. In one embodiment, the base can be selected from one or more of potassium hydroxide, lithium hydroxide, sodium hydroxide, ammonium hydroxide, ethylenediamine, ethanolamine, diethanolamine, triethanolamine, and tetraalkylammonium hydroxide (TAAOH, alkyl = methyl, ethyl, propyl, butyl). The fifth solvent may include one or more of methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, etc. In one embodiment, the molar ratio of the hydroxide ions in the alkali solution to the p-type metal cations contained in the p-type metal salt is (1.2-1.8):1, specifically (1.2-1.6):1, (1.4-1.6):1, (1.4-1.5):1, etc. In one embodiment, before the step S112, it also includes: adding sodium citrate reagent to the p-type metal salt precursor solution. Specifically, the molar ratio of the p-type metal salt precursor to sodium citrate can be 1:0.2-1:0.8, and stirring for 30-60 minutes.

[0069] In the step S112: In one embodiment, an alkali solution is added to the n-type metal salt precursor solution to control the system pH to 11 to 13. The stirring temperature can be 80°C to 90°C, and the stirring time can be 1 to 3 hours, specifically 1 to 1.5 hours, 1.5 to 2 hours, 2 to 2.5 hours, 2.5 to 3 hours, etc. In one embodiment, after the stirring, the mixed system can also be subjected to solid-liquid separation and washing to obtain an n-type metal oxide. Among them, the solid-liquid separation method can include filtration, centrifugation, etc.

[0070] In the step S12: add an organic first metal salt to the first mixture, wherein the mass ratio of the organic first metal salt to the p-type metal oxide is (3-5):10, i.e. (30-50):100, and specifically can be (30-45):100, (35-45):100, (35-40):100, (30-35):100, (45-40):100, etc. The mass ratio can provide enough of the organic first metal salt to form the first metal oxide, so that the composite material includes a gradient valence band position, reduces the hole injection barrier, and improves hole injection and transport. And provide enough organic anions to coordinate and connect to the first metal oxide and the p-type metal oxide, so as to improve the film forming property of the composite material.

[0071] The organic first metal salt includes an organic anion and a first metal cation, wherein the organic anion can refer to the relevant description of the organic group mentioned above, which will not be repeated here.

[0072] In one embodiment, the first metal cation may include a cobalt ion (Co 2+ ), molybdenum ion (Mo 3+ 、Mo 4+ Or Mo 6+ ), chromium ion (Cr 3+ ), manganese ion (Mn 2+). In a specific embodiment, the organic first metal salt includes an organic cobalt salt, which may specifically include one or more of aminosulfonic acid cobalt (II), trifluoromethanesulfonic acid cobalt (II), acetylacetonate cobalt (II), hexafluoroacetylacetonate cobalt (II), etc. In a specific embodiment, the organic first metal salt includes an organic molybdenum salt, which may specifically include acetylacetonate molybdenum, etc. In a specific embodiment, the organic first metal salt includes an organic chromium salt, which may specifically include one or more of benzoylacetonate chromium (III), picolinate chromium (III), acetylacetonate chromium (III), etc. Wherein "III" indicates that the valence state of chromium is +3. In a specific embodiment, the organic first metal salt includes an organic manganese salt, which may specifically include bis (trifluoromethanesulfonyl) imide manganese (II), trifluoromethanesulfonic acid manganese (II), bis (trifluoro-2,4-pentanedione) manganese, acetylacetonate manganese, etc. Wherein "II" indicates that the valence state of manganese is +2.

[0073] In one embodiment, the organic first metal salt is added to the first mixture in the form of a solution. Specifically, the second solvent corresponding to the organic first metal salt may include one or more of water, alcohol solvents, ether solvents, tetrahydrofuran, acetone, chlorobenzene, and toluene. Specifically, the alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, n-butanol, glycerol, etc. The ether solvent includes one or more of methyl ether, ethyl ether, etc. In one embodiment, the second solvent is the same as the first solvent, so that the organic first metal salt can be prevented from mixing with the first mixture to affect the solubility of the first metal salt and the p-type metal salt, improve the mixing uniformity of the first metal salt and the p-type metal salt, and improve the efficiency of the photocatalytic reaction. In a specific embodiment, the first solvent is selected from ethanol, and the second solvent is also selected from ethanol.

[0074] In one embodiment, the organic first metal salt is added to the first mixture in a stirring state to improve the mixing uniformity of the first mixture and the organic first metal salt, thereby promoting the formation of the first metal oxide. In one embodiment, the time of the first light treatment is 1 to 2 hours, specifically 1 to 1.5 hours, 1.5 to 2 hours, etc. In one embodiment, the first light treatment is full-spectrum light treatment, that is, full-band irradiation is used. In another embodiment, the wavelength range of the first light treatment is 200 to 2500nm, such as 200 to 380nm, 380 to 760nm, 760 to 2500nm, etc. One or more. In a specific embodiment, the first light treatment may include one or more of the ultraviolet light band (UV for short, wavelength 200 to 380nm), the visible light band (VL for short, wavelength 380 to 760nm) or the infrared light band (IR for short, wavelength 760 to 2500nm). Further, the light source of the first light treatment may be a single light source or a composite light source formed by multiple light sources. In a specific embodiment, the light source for the first light treatment is a xenon (Xe) lamp. Specifically, the power of the Xe lamp can be 200-500W, such as 200-300W, 300-400W, 400-500W, etc. In one embodiment, during the first light treatment, the first mixture is in a stirring state to improve the mixing uniformity, improve the light uniformity, and improve the heat dissipation. In one embodiment, during the first light treatment of the first mixture, the temperature of the first mixture is maintained at 0-30°C, such as 0-4°C, 4-20°C, 20-25°C, 25-30°C, etc. Specifically, the first mixture can be protected by circulating condensed water to control the temperature of the first mixture within a preset range to avoid excessive temperature of the first mixture due to heat generation from light.

[0075] The time of the second light treatment is 4 to 8 hours, specifically 5 to 8 hours, 5 to 7 hours, 6 to 7 hours, 7 to 8 hours, etc. The second light treatment within the time range can photocatalytically obtain the first metal oxide with a preset loading. In one embodiment, the second light treatment is a full-spectrum light treatment, that is, full-band irradiation is adopted. In one embodiment, the wavelength range of the second light treatment is 200 to 2500nm, such as one or more of 200 to 380nm, 380 to 760nm, 760 to 2500nm, etc. In one embodiment, the second light treatment may include one or more of the ultraviolet light band (UV for short, wavelength 200 to 380nm), the visible light band (VL for short, wavelength 380 to 760nm) or the infrared light band (IR for short, wavelength 760 to 2500nm). In one embodiment, the light source of the second light treatment may be a single light source or a composite light source formed by multiple light sources. In a specific embodiment, the light source of the second light treatment is a xenon (Xe) lamp. Specifically, the power of the Xe lamp may be 200-500W, such as 200-300W, 300-400W, 400-500W, etc.

[0076] In one embodiment, an organic first metal salt is added to the first mixture to obtain a second mixture, and a second light treatment is continued. During the second light treatment of the second mixture, the temperature of the second mixture is maintained at 0 to 30° C., such as 0 to 4° C., 4 to 20° C., 20 to 25° C., 25 to 30° C., etc. Specifically, the second mixture can be protected by circulating condensed water to control the temperature of the second mixture within a preset range to avoid excessive temperature of the second mixture due to heat generation from light.

[0077] In one embodiment, an organic first metal salt is added to the first mixture to obtain a second mixture, and during the process of continuing the second light treatment, the second mixture can be in a stirring state to improve the mixing uniformity and increase the rate of generating the first metal oxide. In one embodiment, after the second light treatment, it also includes: using a cleaning agent to sediment and wash the mixture N times, N is an integer greater than or equal to 2, such as washing three times, etc. The cleaning agent may include one or more of ethyl acetate and acetone. In this embodiment, unreacted reactants, such as unreacted organic first metal salt, etc., can be removed by multiple washings.

[0078] The present application provides a light emitting device, referring to Figure 2 , Figure 2The present application provides a schematic structural diagram of an embodiment of a light-emitting device, wherein the light-emitting device 100 includes a first electrode 10 and a second electrode 20 disposed opposite to each other, and a light-emitting layer 30 disposed between the first electrode 10 and the second electrode 20, and a hole functional layer 40 disposed between the first electrode 10 and the light-emitting layer 30. The material of the hole functional layer 40 includes the composite material provided in the present application, or includes a composite material prepared by the method for preparing the composite material provided in the present application.

[0079] In this embodiment, the material of the hole functional layer 40 includes a composite material, that is, a p-type metal oxide and a first metal oxide, wherein the valence band energy level of the first metal oxide is lower than the valence band energy level of the p-type metal oxide, thereby forming an energy level gradient in the hole functional layer 40, which can reduce the hole injection barrier of the light-emitting device 100, promote the effective injection of holes and improve the hole transmission efficiency. In addition, the composite material is a fully inorganic material, which is less affected by water, oxygen, etc. and has good stability, thereby improving the stability of the hole functional layer 40, thereby improving the stability and life of the light-emitting device 100.

[0080] Furthermore, in the composite material, the surface of the first metal oxide and / or the p-type metal oxide is connected with a negatively charged organic group, and the organic group is coordinated and connected to the surface of the first metal oxide and / or the p-type metal oxide, which can increase the carrier density and promote the injection of holes on the one hand; on the other hand, the organic group is coordinated and connected to the surface of the first metal oxide and / or the p-type metal oxide, and can combine with a large number of oxygen defects on the surface of the first metal oxide and / or the p-type metal oxide, reduce the surface defects of the first metal oxide and / or the p-type metal oxide, and improve the dispersibility and film-forming properties of the composite material, thereby improving the uniformity and density of the film layer of the hole functional layer 40, reducing and avoiding the leakage current phenomenon of the light-emitting device 100, improving the stability of the light-emitting device 100, and reducing the interface barrier between the hole functional layer 40 and the adjacent film layer, thereby further improving the hole injection and transport performance.

[0081] In one embodiment, the material of the hole functional layer 40 is composed of the composite material. Further, the hole functional layer 40 is a single-layer film structure. In this embodiment, the composite material is used as the material of the hole functional layer 40, and the performance of hole injection and hole transport can be achieved through the single-layer hole functional layer 40. In other embodiments, the material of the hole functional layer 40 may include other materials such as metal elements in addition to the composite material.

[0082] In one embodiment, the thickness of the hole functional layer is 10-30 nm, specifically 10-25 nm, 15-25 nm, 15-20 nm, etc. The thickness can form a film layer of uniform thickness, reduce leakage current, and also have good conductivity and improve hole injection.

[0083] In one embodiment, the material of the light-emitting layer 30 is selected from an organic light-emitting material or a quantum dot light-emitting material. The organic light-emitting material can be selected from at least one of diaryl anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light, and DBP fluorescent materials emitting red light;

[0084] The quantum dot luminescent material can be selected from at least one of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound. The II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS , CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, the IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, the The III-V compound is selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, and AlPSb , InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, I At least one of nAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS; the core of the quantum dot with core-shell structure is selected from any one of the above-mentioned single structure quantum dots, and the shell material of the quantum dot with core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductor, or organic-inorganic hybrid perovskite semiconductor; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs +ion, M is a divalent metal cation selected from Pb 2+ Sn 2 + , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - When n=2, the inorganic metal halide octahedron MX6 4- The metal cation M is located at the center of the halogen octahedron, and the organic amine cation B fills the gap between the octahedrons to form an infinitely extended three-dimensional structure. When n>2, the inorganic metal halide octahedron MX6 connected by the top-sharing method 4- It extends in two dimensions to form a layered structure, with an organic amine cation bilayer (protonated monoamine) or an organic amine cation monolayer (protonated diamine) inserted between the layers, and the organic layer and the inorganic layer overlap to form a stable two-dimensional layered structure.

[0085] In one embodiment, the quantum dot luminescent material includes one or more of red quantum dots, green quantum dots, and blue quantum dots. The thickness of the light-emitting layer 30 can be 5 to 100 nm, specifically 5 to 15 nm, 15 to 30 nm, 15 to 35 nm, 25 to 35 nm, 25 to 30 nm, 30 to 50 nm, 50 to 100 nm, etc. In a specific embodiment, the quantum dots are selected from oily quantum dots, and the surface of which is connected with a ligand that is easily soluble in a solvent with a lower polarity, including at least one of an acid ligand, a thiol ligand, an amine ligand, a (oxygen) phosphine ligand, a phospholipid, a soft phosphine, and polyvinyl pyridine. As a specific embodiment, the acid ligand is at least one of deca-acid, undecylenic acid, tetradecanoic acid, oleic acid, and stearic acid; the thiol ligand is at least one of octadecyl mercaptan, dodecyl mercaptan, and octadecyl mercaptan; the amine ligand includes at least one of oleylamine, octadecylamine, and octadecylamine; the (oxygen) phosphine ligand is at least one of trioctylphosphine and trioctylphosphine oxide.

[0086] In one embodiment, the light emitting device 100 may further include an electronic functional layer 50, and the electronic functional layer 50 is disposed between the second electrode 20 and the light emitting layer 30. In one embodiment, the electronic functional layer 50 may include one or both of an electron injection layer 51 and / or an electron transport layer 52; when the electronic functional layer 50 includes the electron injection layer 51 and the electron transport layer 52, the electron injection layer 51 is disposed close to the second electrode 20, and the electron transport layer 52 is disposed close to the light emitting layer 30. In one embodiment, the material of the electron transport layer 52 includes doped or undoped inorganic nanocrystals, wherein the undoped inorganic nanocrystals are selected from one or more of ZnO, TiO2, SnO2, Al2O3, GaO, SiO2, Ga2O3, ZrO2, NiO, ZnS, ZnSe, CdS, InP, GaP, BaTiO3, Cs2CO3, Rb2CO3, RbBr, LiF, LiF / Yb, MgP, and MgF2; the doped inorganic nanocrystals include the undoped inorganic nanocrystals and doping elements, and the doping elements are selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y. In one embodiment, the material of the electron injection layer 51 can be a material known in the art for electron injection layer, for example, it can be selected from but not limited to at least one of LiF, MgP, MgF2, Al2O3, Ga2O3, LiF / Yb, ZnO, Cs2CO3, RbBr, and Rb2CO3. In one embodiment, the first electrode 10 and the second electrode 20 are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes, and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir, and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene, and carbon fibers; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, I At least one of TZO, ICO, AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS. Wherein, " / " represents a stacked structure, for example, the composite electrode AZO / Ag / AZO represents an electrode of a composite structure of three stacked layers consisting of an AZO layer, an Ag layer, and an AZO layer.The first electrode 10 and the second electrode 20 are a pair of electrodes. In one embodiment, the first electrode 10 is an anode, and the second electrode 20 is a cathode.

[0087] The light emitting device 100 further includes a substrate (not shown), which may also be referred to as a substrate. The substrate may be a rigid substrate or a flexible substrate. The rigid substrate may be a ceramic material or various glass materials. The flexible substrate may be a substrate formed of materials such as polyimide film (PI) and its derivatives, polyethylene naphthalate (PEN), phosphoenolpyruvic acid (PEP) or diphenylene ether resin. In one embodiment, the material of the substrate includes glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyether sulfone, or a combination thereof.

[0088] It can be understood that the light emitting device 100 can be an upright light emitting device or an inverted light emitting device. When the light emitting device 100 is an upright light emitting device, the substrate is combined with a side of the first electrode 10 away from the light emitting layer 30. When the light emitting device 100 is an inverted light emitting device, the substrate is combined with a side of the second electrode 20 away from the light emitting layer 30.

[0089] It is understood that, in addition to the above-mentioned functional layers, the light-emitting device 100 may also be provided with some functional layers conventionally used in light-emitting devices that help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer, etc. It is understood that the material and thickness of each layer of the light-emitting device 100 may be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device 100.

[0090] The present application also provides a method for preparing a light emitting device, see Figure 3 , Figure 3 This is a flow chart of an embodiment of a method for preparing a light-emitting device provided in the present application. The light-emitting device prepared in this embodiment is an upright device, and specifically includes the following steps:

[0091] Step S21: providing a preset device, wherein the preset device includes a first electrode;

[0092] Step S22: Arranging a hole functional material on the preset device to form a hole functional layer;

[0093] Step S23: forming a stacked light-emitting layer and a second electrode on the hole functional layer to obtain a light-emitting device.

[0094] In one embodiment, the light-emitting device includes an electronic functional layer, and the step S23 specifically includes: forming a stacked light-emitting layer, an electronic functional layer and a second electrode on the hole functional layer to obtain the light-emitting device.

[0095] See also Figure 4 , Figure 4 This is a flow chart of another embodiment of a method for preparing a light-emitting device provided in the present application. The light-emitting device prepared in this embodiment is an inverted device, and the method for preparing the light-emitting device in this embodiment includes the following steps:

[0096] Step S31: providing a prefabricated device, wherein the prefabricated device comprises a stacked second electrode and a light-emitting layer;

[0097] Step S32: Arranging a hole functional material on the preset device to form a hole functional layer;

[0098] Step S33: forming a stacked first electrode on the hole functional layer to obtain a light-emitting device.

[0099] In one embodiment, the light-emitting device includes an electronic functional layer, and the step S31 specifically includes: providing a prefabricated device, wherein the prefabricated device includes a stacked second electrode, an electronic functional layer, and a light-emitting layer.

[0100] In the above two embodiments, the hole functional material includes the composite material provided in the present application, or includes a composite material obtained by the method for preparing the composite material provided in the present application. For details, please refer to the relevant description above, which will not be repeated here. In a specific embodiment, the hole functional material is the composite material provided in the present application, or is a composite material obtained by the method for preparing the composite material provided in the present application.

[0101] In one embodiment, in step S22 and step S32, the composite material can be disposed on the prefabricated device by a solution method. Specifically, the solution method can be a spin coating method, a printing method, an inkjet printing method, a doctor blade method, a printing method, a dip-pull method, an immersion method, a spray coating method, a roll coating method, a casting method, a slit coating method, and a strip coating method. In a specific embodiment, in step S22 and step S32, the composite material is disposed on the preset device to form a hole functional layer, including: disposing a third mixture on the preset device, wherein the third mixture includes the composite material and a third solvent. Specifically, the third solvent may include an alcohol solvent, specifically, one or more of methanol, ethanol, isopropanol, n-butanol, ethylene glycol, glycerol, and the like. Further, the concentration of the composite material in the third mixture can be 20-40 mg / mL, specifically 20-35 mg / mL, 25-35 mg / mL, 25-30 mg / mL, 20-25 mg / mL, 35-40 mg / mL, etc. In a specific embodiment, the concentration of the composite material is 30 mg / mL. Therefore, the concentration range can form a better film layer and reduce the waste of solvent.

[0102] After the third mixture is prepared by the solution method, it is necessary to dry it to remove the third solvent. The drying can be heating drying or vacuum drying. The heating drying temperature can be 60 to 80°C and the time can be 20 to 60 minutes. The vacuum drying pressure is 10 -1 ~10 -2 Pa. Furthermore, the vacuum drying temperature may be room temperature (about 25° C.). In other embodiments, the composite material may be disposed on the prefabricated device by other methods known in the art, such as sputtering.

[0103] In each embodiment of the above-mentioned preparation method, the electron transport layer, hole functional layer, light-emitting layer, first electrode, second electrode, etc. can refer to the corresponding description of the light-emitting device 100 in the above text, and will not be repeated here.

[0104] In the light-emitting device provided in the present application, the preparation methods of the first electrode, the second electrode, the light-emitting layer, the hole functional layer, the electron functional layer and other film layers can be implemented by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction method, anodization method, electrolytic deposition method, and coprecipitation method. The physical method includes physical plating method and solution method, among which the physical plating method includes: thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion plating method, physical vapor deposition method, atomic layer deposition method, pulsed laser deposition method, etc.; the solution method can be spin coating, printing method, inkjet printing method, blade coating method, printing method, dip pulling method, immersion method, spraying method, roll coating method, casting method, slit coating method and strip coating method, etc.

[0105] It is understood that the method for preparing the light-emitting device may further include a packaging step, and the packaging material used for packaging may be selected from at least one of UV glue, metal film, and glass glue. In a specific embodiment, the packaging material may be acrylic resin or epoxy resin. The packaging may be machine packaging or manual packaging, and may be sealed with ultraviolet curing glue. The concentration of oxygen and water in the environment of the packaging step is less than 0.1ppm to ensure the stability of the light-emitting device.

[0106] The present application also relates to a display device, which includes the light-emitting device provided in the present application. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.

[0107] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0108] Embodiment 1:

[0109] This embodiment provides a method for preparing a composite material and the prepared composite material, wherein the preparation method specifically comprises the following steps:

[0110] Step 1: Add copper chloride to ethanol to obtain 30 mL of 1 M metal salt precursor solution, and add 0.015 mmol of sodium citrate thereto to obtain a mixed solution A. Weigh an appropriate amount of sodium hydroxide and dissolve it in 5 mL of ethanol solution to obtain an alkali solution;

[0111] Step 2: Follow OH - The molar ratio of copper ions to iodine is 1.8:1, and the alkali solution is added to the mixed solution A to form a mixed solution with a pH of 13, and then stirred at 80° C. for 1 hour to obtain a copper oxide nanoparticle solution. The reaction product is filtered, centrifuged, washed, and finally dispersed in ethanol.

[0112] Step 3: Take 10 mL of the 40 mg / mL copper oxide ethanol solution and irradiate the solution under a 300 W Xe lamp (full spectrum) for 1 hour under the protection of circulating condensed water at 4°C while continuously stirring.

[0113] Step 4: Under continuous light irradiation, add 12 mg / mL aminosulfonate cobalt (II) ethanol solution to the solution in step 3, and continue irradiation for 4 hours, during which it is carried out under the protection of circulating condensed water at 4°C. The mass ratio of aminosulfonate to copper oxide is 30:100. After photodeposition, the above solution is washed three times by precipitation in excess ethyl acetate or acetone to wash away the excess cobalt salt to obtain a composite material.

[0114] Embodiment 2:

[0115] This embodiment is substantially the same as embodiment 1, except that in step 4, the mass ratio of cobalt sulfamate to copper oxide is 40:100.

[0116] Embodiment 3:

[0117] This embodiment is substantially the same as embodiment 1, except that in step 4, the mass ratio of cobalt sulfamate to copper oxide is 50:100.

[0118] Embodiment 4:

[0119] This example is substantially the same as Example 2, except that in step 4, cobalt trifluoromethanesulfonate is added instead of cobalt (II) sulfamate in Example 1.

[0120] Embodiment 5:

[0121] This embodiment is substantially the same as embodiment 2, except that in step 4, cobalt acetylacetonate is added instead of cobalt (II) sulfamate in embodiment 1.

[0122] Embodiment 6:

[0123] This embodiment is substantially the same as embodiment 2, except that in step 4, molybdenum acetylacetonate is added instead of the cobalt (II) sulfamate of embodiment 1.

[0124] Embodiment 7:

[0125] This embodiment is substantially the same as embodiment 2, except that in step 4, chromium benzoylacetonate is added instead of cobalt (II) sulfamate in embodiment 1.

[0126] Embodiment 8:

[0127] This embodiment is substantially the same as embodiment 2, except that in step 4, chromium acetylacetonate is added instead of cobalt (II) sulfamate in embodiment 1.

[0128] Embodiment 9:

[0129] This example is substantially the same as Example 2, except that in step 4, manganese trifluoromethanesulfonate is added instead of cobalt (II) sulfamate in Example 1.

[0130] Embodiment 10:

[0131] This example is substantially the same as Example 2, except that in step 4, manganese bis(trifluoromethanesulfonyl)imide is added instead of cobalt(II) sulfamate in Example 1.

[0132] Embodiment 11:

[0133] This embodiment is substantially the same as embodiment 1, except that in step 4, the mass ratio of cobalt sulfamate to copper oxide is 20:100.

[0134] Embodiment 12:

[0135] This embodiment is substantially the same as embodiment 1, except that in step 4, the mass ratio of cobalt sulfamate to copper oxide is 60:100.

[0136] Embodiment 13:

[0137] This embodiment is substantially the same as embodiment 6, except that steps 1 and 2 are not performed, CrO3 is used in step 3 instead of copper oxide, and a composite material including CrO3 and molybdenum oxide is finally obtained.

[0138] Embodiment 14:

[0139] This embodiment is substantially the same as embodiment 6, except that steps 1 and 2 are not performed, CoO is used in step 3 instead of copper oxide, and a composite material including CoO and molybdenum oxide is finally obtained.

[0140] Embodiment 15:

[0141] This embodiment is substantially the same as embodiment 8, except that steps 1 and 2 are not performed, MnO is used in step 3 instead of copper oxide, and a composite material including MnO and chromium oxide is finally obtained.

[0142] Embodiment 16:

[0143] This embodiment is basically the same as embodiment 6, except that steps 1 and 2 are not performed, and In2O3 is used in step 3 instead of copper oxide, and a composite material including In2O3 and molybdenum oxide is finally obtained.

[0144] Comparative Example 1:

[0145] This embodiment is basically the same as embodiment 1, except that after obtaining copper oxide nanoparticles in step 2, steps 3 and 4 are not performed.

[0146] Comparative Example 2:

[0147] This example is basically the same as Example 1, except that: after obtaining copper oxide nanoparticles in step 2, 10 mL of the 40 mg / mL copper oxide nanomaterial ethanol solution is taken, and 10 mL of the 16 mg / mL cobalt oxide material ethanol solution is added. The solution is stirred for 1 hour to obtain a copper oxide-cobalt oxide mixed material;

[0148] Wherein, the preparation method of cobalt oxide is as follows:

[0149] An appropriate amount of cobalt chloride is dispersed in 25 mL of ethanol to form a cobalt chloride solution with a concentration of 1 mol / L, and an appropriate amount of sodium hydroxide is dissolved in 5 mL of ethanol to prepare a sodium hydroxide solution with a concentration of 1 mol / L. The sodium hydroxide solution is added dropwise to the cobalt chloride solution until the molar ratio of cobalt ion: OH- is 1:1.7, forming a mixed system with a pH of 13, and then the mixed system is heat-treated under stirring at a temperature of 60°C and a time of 3 hours to obtain a cobalt oxide solution.

[0150] Comparative Example 3:

[0151] This embodiment is basically the same as Comparative Example 2, except that molybdenum oxide is used instead of cobalt oxide, and the copper oxide-molybdenum oxide mixed material is finally obtained;

[0152] Wherein, the preparation method of molybdenum oxide is as follows:

[0153] 10 mmol of ammonium molybdate and 300 mmol of thiourea were added into 350 mL of ionized water, and the mixture was placed in a reactor at 110° C. to react for 2 h, and finally filtered with a 0.22 μm microporous filter membrane to obtain a molybdenum oxide ethanol solution.

[0154] Comparative Example 4:

[0155] This embodiment is substantially the same as Comparative Example 2, except that chromium oxide is used instead of cobalt oxide, and the resulting copper oxide-chromium oxide mixed material is obtained;

[0156] Wherein, the preparation method of chromium oxide is as follows:

[0157] 70 mg of chromium chloride was dissolved in 15 ml of anhydrous ethanol, reacted in a reactor at 120° C. for 2 hours, and after cooling, centrifuged at a speed greater than 10,000 rpm for more than 10 minutes to obtain a supernatant solution after centrifugation to obtain a chromium oxide ethanol solution.

[0158] Comparative Example 5:

[0159] This embodiment is basically the same as Comparative Example 2, except that manganese oxide is used instead of cobalt oxide, and the copper oxide-manganese oxide mixed material is finally obtained;

[0160] Wherein, the preparation method of manganese oxide is as follows:

[0161] Weigh 150 mg of potassium permanganate and mix with 50 mL of anhydrous ethanol to obtain a precursor solution. Weigh 10 g of ammonium bicarbonate, place the precursor solution and ammonium bicarbonate in a closed environment (vacuum drying oven) in their respective beakers, and heat at 40° C. to react. After the reaction is completed, centrifuge at 15,000 rpm for ten minutes to obtain an ethanol solution of manganese oxide nanoparticles.

[0162] Device Example 1

[0163] The device embodiment provides a quantum dot light emitting diode and a method for preparing the same, which specifically includes the following steps.

[0164] Step 1: Place the ITO glass sheet in a glass dish filled with ethanol solution, and ultrasonicate with acetone, deionized water, and ethanol for 20 minutes respectively, and then blow dry with a nitrogen gun; then place the cleaned ITO glass sheet in oxygen plasma for further cleaning for 10 minutes; continue to use UV-ozone to treat the surface of the ITO substrate for 15 minutes;

[0165] Step 2: Spin-coat the cleaned ITO glass sheets with a solution of the composite material of Example 1 (with a concentration of 30 mg / mL) in air, and anneal at 60° C. for 5 minutes in a glove box after spin coating to obtain a hole functional layer with a thickness of 30 nm;

[0166] Step 3: Spin-coat Cd0.08ZnSe / Cd0.6Zn0.6Se / ZnSe / ZnS blue quantum dots on the hole transport layer at a spin-coating speed of 2000 r / min for 30 seconds; after spin-coating, anneal at 60 degrees Celsius in a glove box for 5 minutes to obtain a light-emitting layer with a thickness of 25 nm;

[0167] Step 4: Spin-coat a ZMO ethanol solution (concentration of 30 mg / mL) on the light-emitting layer at a rotation speed of 3000 r / min for 30 seconds, and dry to obtain an electron transport layer with a thickness of 30 nm.

[0168] Step 5: Place the sample prepared in step 4 into a vacuum chamber, evaporate a top silver electrode with a thickness of 100 nm, and encapsulate.

[0169] Device Examples 2-16

[0170] This device embodiment is basically the same as device embodiment 1, and the only difference is that in step 2, the composite materials of embodiments 2-16 are used respectively.

[0171] Device Comparison Examples 1-5

[0172] The device comparative example 5 is basically the same as the device embodiment 1, and the only difference is that: the copper oxide ethanol solution in comparative example 1 is directly used in step 2, the solution of the copper oxide-cobalt oxide mixed material in comparative example 2 is used in step 2, the solution of the copper oxide-molybdenum oxide mixed material in comparative example 3 is used in step 2, the solution of the copper oxide-chromium oxide mixed material in comparative example 4 is used in step 2, and the solution of the copper oxide-manganese oxide mixed material in comparative example 5 is used in step 2.

[0173] Test 1:

[0174] In the process of preparing the quantum dot light-emitting diodes in device comparative example 1 and device example 2, after preparing the hole functional layer, an AFM (atomic force microscope) roughness test was performed on the hole functional layer, and the roughness of the hole functional layer was obtained. Figure 5 and Figure 6 ,in, Figure 5 and Figure 6 The AFM images of the hole functional layer in device comparative example 1 and device embodiment 2 respectively correspond to each other.

[0175] Depend on Figure 5 and Figure 6 It can be seen that the arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the hole functional layer in device embodiment 2 are respectively much smaller than the arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the hole injection layer in device comparison example 1, indicating that the hole functional layer formed by the composite material provided in the present application has good film-forming property and surface uniformity. The provided composite material has good film-forming property, which may be due to the fact that in the process of in-situ photocatalytic formation of the first metal oxide by the p-type metal oxide, on the one hand, the bonding tightness between the first metal oxide and the p-type metal oxide can be improved, and on the other hand, the organic anions are connected to the surfaces of the first metal oxide and the p-type metal oxide, and can be combined with a large number of oxygen defects on the surfaces of the first metal oxide and the p-type metal oxide, and effectively reduce the aggregation and regrowth of the first metal oxide particles and the p-type metal oxide particles, thereby improving the film-forming property of the composite material. It is also possible that during the preparation of the composite material, the holes (h+) generated by photocatalysis can effectively fill the defects on the surface of the p-type metal oxide (such as oxygen vacancies, etc.), play a role in passivating the p-type metal oxide, and can effectively avoid the regrowth of p-type metal oxide nanoparticles, improve the uniformity of the particles in the composite material, reduce agglomeration, and thus improve the film-forming property of the composite material.

[0176] Test 2:

[0177] The quantum dot light-emitting diodes of device examples 1-13 and device comparative examples 1-5 were tested for external quantum efficiency EQE and lifetime, and the data are shown in Table 1. Figure 7-10 , Figure 7 EQE-J curves of device embodiments 1-5 and comparative examples 1-2, Figure 8 EQE-J curves of device example 6 and comparative examples 1 and 3, Fig. 9 EQE-J curves of device embodiments 7-8 and comparative examples 1 and 4, Fig.10 EQE-J curves of device examples 9-10 and comparative examples 1 and 5.

[0178] (1) The detection method of external quantum efficiency EQE is:

[0179] The ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, expressed in %, is an important parameter for measuring the quality of electroluminescent devices and can be obtained by measuring with an EQE optical test instrument. The specific calculation formula is as follows:

[0180]

[0181] Among them, η e is the light output coupling efficiency, η γ is the ratio of the number of recombined carriers to the number of injected carriers, x is the ratio of the number of excitons that generate photons to the total number of excitons, K R is the radiation process rate, K NR is the rate of the non-radiative process.

[0182] Test conditions: carried out at room temperature, air humidity is 30-60%.

[0183] (2) The test method for life span T95@1000nit is: the time required for the brightness of the device to decrease to a certain proportion of the maximum brightness under constant current or voltage drive. The time when the brightness drops to 95% of the maximum brightness is defined as T95, and this life span is the measured life span. In order to shorten the test cycle, the device life span test is usually carried out at high brightness by accelerating device aging, and the life span at high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula. For example, the life span at 1000nit is calculated as T95@1000nit. The specific calculation formula is as follows:

[0184]

[0185] Among them, T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, and A is the acceleration factor.

[0186] Test 3:

[0187] According to the quantum dot light-emitting diodes of device examples 1-13 and device comparison examples 1-5, single hole devices (HOD) are prepared respectively, wherein the preparation method of the single hole device (HOD) is substantially the same as the preparation method of the corresponding complete QLED device, except that the electron transport layer is not prepared, and the obtained single hole device does not include an electron transport layer. The device structure of the single hole device (HOD) is: glass substrate / ITO / hole functional layer / QD light-emitting layer / Ag electrode.

[0188] The hole injection performance test method is:

[0189] A QLED efficiency test system was built by controlling QE PRO and Keithley 2400 through LabView. The system was used to test the current density-voltage curve (JV curve) of the single hole device (HOD). Figure 11-12 , Fig.11 is the JV curve of the single hole device of device examples 1-10, Fig.12 JV curves of single hole devices of device example 6 and comparative examples 1-5.

[0190] Through the current density-voltage curve, the space charge limited current (SCLC) region in the curve is obtained, and then according to the formula J = (9 / 8)ε r ε0μeV 2 / d 3 The hole mobility is calculated and the data is shown in Table 1. Where J represents the current density, with the unit of mAcm -2 ; εr represents the relative dielectric constant, ε0 represents the vacuum dielectric constant; μ e Indicates hole mobility, unit: cm 2 V -1 s -1 ; V represents the driving voltage, unit is V; d represents the film thickness, unit is m.

[0191] The working voltage of the HOD device in the steady state is taken for comparison. The working voltage in the steady state refers to the working voltage of the device in the relatively balanced stage when the device runs for more than 6 hours during the device life test. The voltage after 10 hours is taken for comparison. The working voltage data of the HOD device is shown in Table 1. The voltage-time curve of the single hole device (HOD) is shown in Table 1. Figure 13-16 . Fig.13 : are the voltage-time curves of the single hole devices of device embodiments 1-5 and comparative examples 1-2, Fig.14 is the voltage-time curve of the single hole device of device example 6 and comparative examples 1 and 3, Fig.15 : are the voltage-time curves of the single hole devices of device examples 7-8 and comparative examples 1 and 4, Fig.16 The voltage-time curves of the single hole devices of device examples 9-10 and comparative examples 1 and 5 are shown.

[0192] Test 4:

[0193] The valence band positions of the copper oxide nanoparticles, cobalt oxide nanoparticles, molybdenum oxide nanoparticles, chromium oxide nanoparticles and manganese oxide nanoparticles prepared in Comparative Examples 1, 2 and 3 were measured respectively. Figure 17-21 , Figure 17-21 These are the valence band position diagrams of copper oxide, molybdenum oxide, manganese oxide, chromium oxide, and cobalt oxide respectively.

[0194] Method for determining the valence band position: Use nanoparticles to prepare a dry film as a test sample. The film size is about 6*6mm and the thickness is less than 2mm. The Vance band (VB) spectrum is measured using a monochromatic He I light source (21.2eV) and a VG Scienta R4000 analyzer. The sample bias is -5V, and the secondary electron cutoff edge spectrum (SEC) is tested.

[0195] Table 1

[0196]

[0197]

[0198] It can be seen from Table 1 that compared with device comparison examples 1-5, the external quantum efficiency and lifespan of device embodiments 1-16 are improved, indicating that the composite material provided in the present application as the material of the hole functional layer can have good hole transport and hole injection performance, improve the hole mobility of the light-emitting device, thereby improving the carrier injection balance of the light-emitting device, and further improving the external quantum efficiency and lifespan of the device.

[0199] It can be seen from device embodiments 1-3 and 11-12 that in the preparation process of the composite material, the mass ratio of the organic first metal salt to the p-type metal oxide is relatively small (for example, 20:100), which may have a small improvement in the performance of hole injection, and the amount of organic anions is also relatively small, so that the effect on the film formation uniformity and surface smoothness of the hole functional layer is relatively small; while the mass ratio of the organic first metal salt to the p-type metal oxide is relatively large (for example, 60:100), so that relatively more first metal oxide is produced, and relatively more organic anions are introduced, which may lead to a decrease in the conductivity of the device, affecting the efficiency of the light-emitting device to a certain extent.

[0200] from Figure 13-16 It can be seen that compared with the HOD device corresponding to the device comparison example, the HOD device corresponding to the device embodiment has a relatively low operating voltage, indicating that the present application provides a light-emitting device, wherein the hole functional layer includes the composite material provided by the present application, which can effectively improve the hole injection of the device. Figure 11-12 As can be seen from the data in Table 1, compared with the HOD device corresponding to the device comparison example, the HOD device corresponding to the device embodiment has better hole mobility, and the light-emitting device provided in the present application can improve hole injection, thereby improving device efficiency and life.

[0201] from Figure 17-21It can be seen that the valence band position of the introduced first metal oxide is between -4.97 and -5.20 eV, which is lower than the valence band position of the p-type metal oxide. For example, the valence band position of copper oxide is -4.86 eV, thereby forming an energy level gradient in the hole functional layer, which can further reduce the hole injection barrier, promote the effective injection of holes, and improve the luminescence efficiency of the device.

[0202] The composite materials and their preparation methods, light-emitting devices and their preparation methods, and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A composite material, characterized in that: The invention comprises a p-type metal oxide and a first metal oxide, wherein a valence band energy level of the first metal oxide is lower than a valence band energy level of the p-type metal oxide.

2. The composite material according to claim 1, characterized in that The valence band energy level of the p-type metal oxide is between -4.7 and -5.2 eV; and / or, the valence band energy level of the first metal oxide is between -4.90 and -5.20 eV; and / or, the mass ratio of the first metal oxide to the p-type metal oxide is 1 to 2:5; And / or, a negatively charged organic group is connected to the surface of the first metal oxide and / or the p-type metal oxide, and the organic group has one or more of the following structures: Wherein, each occurrence of R1, R2, R3, and R4 is independently selected from one or more of H, D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.

3. The composite material according to claim 2, characterized in that Each occurrence of R1, R2, R3, and R4 is independently selected from -NH2, C1-C10 alkyl, C1-C10 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and aryl having 5 to 24 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl; and / or, the first metal oxide is connected to the p-type metal oxide; And / or, the p-type metal oxide includes one or more of CuO, MnO, In2O3, CoO, CrO3; and / or, the average particle size of the p-type metal oxide is 3 to 10 nm; And / or, the first metal oxide includes one or more of cobalt oxide, molybdenum oxide, chromium oxide, and manganese oxide; And / or, the average particle size of the first metal oxide is 2 to 5 nm.

4. The composite material according to claim 3, characterized in that The organic group has one or more of the following structures:

5. A method for preparing a composite material, characterized in that: include: Providing a first mixture, wherein the first mixture includes a p-type metal oxide and a first solvent, wherein the first solvent includes a hole sacrificial agent; After the first mixture is subjected to a first light treatment, an organic first metal salt is added to the first mixture, and the first mixture is subjected to a second light treatment to obtain a composite material; The valence band energy level of the first metal oxide converted from the organic first metal salt is lower than the valence band energy level of the p-type metal oxide.

6. The preparation method according to claim 5, characterized in that: The valence band energy level of the p-type metal oxide is between -4.7 and -5.2 eV; and / or, the average particle size of the p-type metal oxide is 3 to 10 nm; and / or, the mass ratio of the first organic metal salt to the p-type metal oxide is (3-5):10; and / or, the concentration of the p-type metal oxide in the first mixture is 40 to 80 mg / mL; And / or, the organic first metal salt includes an organic anion and a first metal cation, wherein the organic anion may include one or more of the following structural formulas: Wherein, each occurrence of R1, R2, R3, and R4 is independently selected from one or more of H, D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.

7. The preparation method according to claim 6, characterized in that: The organic anion includes one or more of the following structural formulas: And / or, the first metal cation includes one or more of cobalt ions, molybdenum ions, chromium ions, and manganese ions; and / or, the first solvent comprises one or more of an alcohol solvent having 1 to 8 carbon atoms, an ether solvent having 1 to 8 carbon atoms, tetrahydrofuran, acetone, chlorobenzene, and toluene; And / or, the hole sacrificial agent includes one or more of acetonitrile, triethylamine, triethanolamine, sodium sulfite, methanol, and ethanol; And / or, the mass ratio of the hole sacrificial agent to the p-type metal oxide is (0.5-1.5):

5.

8. The preparation method according to claim 5, characterized in that: The first light treatment adopts full spectrum irradiation; And / or, the first light treatment lasts for 1 to 2 hours; and / or, during the first light treatment of the first mixture, the temperature of the first mixture is maintained at 0-30° C.; and / or, during the first light irradiation process, the first mixture is in a stirring state; And / or, the second light treatment uses full spectrum irradiation; And / or, the second light treatment time is 4 to 8 hours; And / or, after adding the first organic metal salt to the first mixture, a second mixture is obtained, and during the second light treatment of the second mixture, the temperature of the second mixture is maintained at 0-30° C. and the second mixture is in a stirring state.

9. A photoelectric device, characterized in that: include: A hole functional layer, wherein the material of the hole functional layer comprises the composite material as described in any one of claims 1 to 4, or comprises a composite material prepared by the method for preparing the composite material as described in any one of claims 5 to 8.

10. A display device, characterized in that: Comprising the optoelectronic device as claimed in claim 9.